Mediator Interactions in Acute Respiratory Distress Syndrome - K. A. Pavlov; Ye. A. Dubova; O. D. Mishnyov; A. I. Shchegolev (Общая реаниматология)
The review of literature covers the interaction of numerous mediators that are initiators and major motive forces of the occurrence and development of acute respiratory distress syndrome (ARDS). The major mediator families include cytokines, mediators of lipid origin, components of the extracellular matrix, mediators of the oxidative and antioxidative systems, proteinases, and components of the coagulation system. The representatives of each of the above families play an important role at each developmental stage of ARDS: an increase in the permeability of pulmonary capillaries, chemotaxis of neutrophilic granulocytes, macrophages, and lymphocytes, secondary damage to endotheliocytes, pulmonary epithelium and surfactant, occurrence of pulmonary hypertension, and development of pulmonary fibrosis in late-stage ARDS. The intensity of clinical manifestations depends on the interaction between pro- and anti-inflammatory mediators, which starts at the earliest stages of their development. Searches for specific antagonists of proinflammatory mediators and their receptors were noted to be of importance for further clinical application and, first all, development of more effective treatments for ARDS.